Dois ensaios sobre precificação de ativos - Marconi, Tamyris (2016)
Find fair (according to some criterion) prices for assets in financial markets is one of the most important pillars of Finance Theory. To accomplish this, the Asset Pricing Theory has a mathematical formulation, based mainly on Probability Theory. In this dissertation we present such theory, which is essentially based on mar- tingales, important objects of Probability Theory. Alternatively, we also present an Asset Pricing Theory based on the Coherence Theory of Bruno de Finetti in order to compare, informally, such approaches.